Edukasi Gizi sebagai Upaya Peningkatan Pengetahuan Pencegahan Stunting pada Kader Posyandu dalam Program “Desa Emas: Percepatan Penurunan Stunting” - Auresa Caesarputriaulya Willmart; Fransisca Nimas Restu Krissandiani; Siti Rahayu Nadhiroh (Universitas Airlangga, 2024)
Background: One form of promotive and preventive efforts to accelerate the reduction of stunting is active role of posyandu cadres in carrying out nutrition counseling to mothers of toddlers to increase knowledge related to nutrition so as to achieve optimal public health status. Therefore, efforts are needed to increase the knowledge of posyandu cadres, one of which can be done through nutrition education. Objective: This study aims to provide nutrition education as an effort to increase posyandu cadres' knowledge regarding stunting prevention as a form of integrated community service in the